Profil Pasien Luka Bakar di Rumah Sakit Umum Daerah Waikabubak, Sumba Barat , Indonesia Tahun 2019–2021 - Djunaedi, Angela; Sukmadi Karjosukarso, Adityas (Cermin Dunia Kedokteran, 2024)
Introduction: West Sumba, East Nusa Tenggara, is known as one of the areas with limited healthcare facilities. Burn injury can happen to anyone from all sorts of backgrounds. This research was conducted to observe the pattern of burn injury in Waikabubak General Hospital. Methods: A retrospective descriptive study was conducted using medical records data at Waikabubak General Hospital from 2019-2021. Results: Thirty-five burn injuries patients were evaluated. The majority of patients were male (71%) and ranging from the age of < 2 - 12 years old (54%). Scald burns by hot water were the most common cause (54%). The extremities were the common site of injury (34%), with the mean total body surface area (TBSA) was 16.8%, and the most common complications were severe dehydration (9%) and death (9%). The main comorbid disease was epilepsy (11%), most had a length of stay of 5-10 days, with an average of 6 days, and the most frequent intervention was debridement (54%). Most patients were discharged with improved condition (74%). Conclusion: Children and patients with epilepsy were at risk. It is important to equip caregivers and family members with specific preventive strategies and first aid training programs.